Whole-genome sequencing of streptomycin-resistant Mycobacterium tuberculosis strain SBH145 from Sabah, Malaysia - Zainal Arifin Mustapha; Jaeyres Jani; Cheronie Shely Stanis; Dg Syahidah Nadiah Abdull Majid; Chin, Kai Ling; Roddy Teo; Kamruddin Ahmed (American Society for Microbiology, 2022)
This paper reports on the whole-genome sequencing of a streptomycin-resistant Mycobacterium tuberculosis strain that was isolated from a patient with pulmonary tuberculosis in Sabah state of Malaysian Borneo. The strain belongs to the EAI2-Manila family of lineage 1 and is clustered with M. tuberculosis strains from the Philippines, India, and Taiwan.